Research into the Aspects of Cybersecurity Education in Higher Education - Saharinen, Karo (2023)
The importance of cybersecurity has increased due to the digitalization of society. In the last 10 years, the Finnish Cybersecurity Strategy has been released twice in 2013 and 2019. The newest cybersecurity strategy states as its third chapter the development of cybersecurity competence within society. To amend the strategy, an implementation plan was released for the years 2017–2019, and a development program was released in 2021. The first theme of the development program is to ensure top class knowledge and development of cyber security education in Finland. During this time period, several degree programmes concentrating on cybersecurity have been established in Finland. In vocational education, the basic degree in Information and Communication Technology has been updated to contain the maintenance of cybersecurity as an elective module. In addition, several other steps have been taken to increase the knowledge around cybersecurity nationally. This study concentrates on researching cybersecurity education from different perspectives. The study was scoped into cybersecurity education within the higher education institutions. The goal was to find and establish solid fundamentals on which the competences, knowledge, and skills, could be based. Viewpoints on national cybersecurity education were also researched internationally by comparing cybersecurity degrees abroad through a unified analysis framework. The research also included theses done within these degree programmes as well as graduate employment. When vocational education was updated to include cybersecurity, the decision was made to research how the industry needed the competences developed there. As a conclusion, the framework chosen within this research was deemed valid for curriculum development and as an analysis tool for several aspects of cybersecurity education. This research also verified what kind of education would be most beneficial for a student focusing on cybersecurity. The dissertation also provides data and researched viewpoints to curriculum developers on how and what to establish their competence structure in degree programmes focusing on cybersecurity. Keywords: cybersecurity, cybersecurity education, pedagogy